Motivation of Airbnb Host: Evidence From Pre-COVID Study In Sabah, Malaysia - Izyanti Awang Razli; Zaiton Osman; Phang Ing Grace (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
Airbnb, or also known as peer-to-peer accommodation has gained popularity in the hospitality industry. By using an online platform to align a guest's different needs with a host, a unique customized accommodation experience can be created. The guest side on motivation, perception, and satisfaction in participating in this platform have been often investigated. This paper explores the host perspective on what motivates them to become Airbnb host in the context of Sabah, Malaysia. Qualitative approach was selected with semi-structured interview were conducted among 16 Airbnb host located all over the state, in a six-month pre-COVID period (late 2019 to early 2020). Transcriptions were coded, analyzed, and structured into qualitative narrations. Using a Social Exchange Theory, intrinsic factors such as social benefits, passion on learning new culture, enjoyment in receiving recognition were identified in motivating host to participate in Airbnb. Other includes, extrinsic motivation, such as economic and monetary reasons. The findings provide insight into the host viewpoint, resulting in outcomes that can be used to draw more hosts that can provide a high-quality experience for guests in the future. At the same time, the research results are expected to contribute to sustainability of the peer-to-peer accommodation platform. Furthermore, this study recommends having a comparative study pre vs post COVID period to explore the motivations factors that could be affected by the pandemic.